Financial statement analysis : a practitioner's guide - Fridson, Martin S.; Alvarez, Fernando, 1964- (Wiley finance series., 2022)
The updated, real-world guide to interpreting and unpacking GAAP and non-GAAP financial statements In Financial Statement Analysis, 5th Edition, leading investment authority Martin Fridson returns with Fernando Alvarez to provide the analytical framework you need to scrutinize financial statements, whether you're evaluating a company's stock price or determining valuations for a merger or acquisition. Rather than taking financial statements at face value, you'll learn practical and straightforward analytical techniques for uncovering the reality behind the numbers. This fully revised and up-to-date 5th Edition offers fresh information that will help you to evaluate financial statements in today's volatile markets and uncertain economy. The declining connection between GAAP earnings and stock prices has introduced a need to discriminate between instructive and misleading non-GAAP alternatives. This book integrates the alternatives and provides guidance on understanding the extent to which non-GAAP reports, particularly from US companies, may be biased. Understanding financial statements is an essential skill for business professionals and investors. Most books on the subject proceed from the questionable premise that companies' objective is to present a true picture of their financial condition. A safer assumption is that they seek to minimize the cost of raising capital by portraying themselves in the most favorable light possible. Financial Statement Analysis teaches readers the tricks that companies use to mislead, so readers can more clearly interpret statements. Learn how to read and understand financial statements prepared according to GAAP and non-GAAP standards Compare CFROI, EVA, Valens, and other non-GAAP methodologies to determine how accurate companies' reports are Improve your business decision making, stock valuations, or merger and acquisition strategy Develop the essential skill of quickly and accurately gathering and assessing information from financial statements of all types Professional analysts, investors, and students will gain valuable knowledge from this updated edition of the popular guide. Filled with real-life examples and expert advice, Financial Statement Analysis, 5th Edition, will help you interpret and unpack financial statements.